Why do women fall for money? The Effect of Gender Ideology and Culture on the Mate Preference for Resources - Thomas, Marina (Student Undergraduate Research E-journal!, 2016)
Women generally value a potential partner's earning capacity more than men. Patriarchal gender ideologies could explain why even financially independent females prefer a mate with resources and would also hold for migrants from more to less patriarchal countries. To examine the role of gender traditionalism and ethnicity, the present online study compared the preference for a mate with financial resources in 406 Turkish, Dutch and German students and Turkish migrants in Germany and the Netherlands. As expected, more traditional females, and women from more patriarchal cultures, found resources more important than less traditional females, and women from more egalitarian cultures.